Ecological genomics predicts climate vulnerability in an endangered southwestern songbird. (9th May 2018) - Ruegg, Kristen; Bay, Rachael A.; Anderson, Eric C.; Saracco, James F.; Harrigan, Ryan J.; Whitfield, Mary; Paxton, Eben H.; Smith, Thomas B.
Abstract: Few regions have been more severely impacted by climate change in the USA than the Desert Southwest. Here, we use ecological genomics to assess the potential for adaptation to rising global temperatures in a widespread songbird, the willow flycatcher ( Empidonax traillii ), and find the endangered desert southwestern subspecies ( E. t. extimus ) most vulnerable to future climate change. Highly significant correlations between present abundance and estimates of genomic vulnerability – the mismatch between current and predicted future genotype–environment relationships – indicate small, fragmented populations of the southwestern willow flycatcher will have to adapt most to keep pace with climate change. Links between climate‐associated genotypes and genes important to thermal tolerance in birds provide a potential mechanism for adaptation to temperature extremes. Our results demonstrate that the incorporation of genotype–environment relationships into landscape‐scale models of climate vulnerability can facilitate more precise predictions of climate impacts and help guide conservation in threatened and endangered groups.